Development of Risk Assessment Framework for Political Risk Guarantee in Public-Private Partnership Projects - Permana, Andre; Kong, Robert Tiong Lee (PT Penjaminan Infrastruktur Indonesia (Persero), 2018)
In Public-Private Partnership (PPP) projects, guarantees can be regarded as a government fiscal support. Due to its uncertainty, one of the key challenges in guarantee valuation is to define appropriate assumptions for underlying risk factors since infrastructure projects are not assets that can be explicitly linked to an observable market price. While very few governments formally measure them, it is also found that sometimes the assessment on political risk covered by the guarantees is highly subjective and ambiguous. This paper proposes a methodology that combined quantitative and qualitative approach for contingent liabilities assessment for PPP infrastructure projects with focus on political risk. It uses fuzzy sets based risk assessment that quantifies expert opinion on likelihood and impact of risk factors into an input to quantitative risk analysis. A particular developing country is chosen so that the proposed methodology can be applied according to the country and infrastructure sectors specific context.